2004
DOI: 10.1111/j.1365-2141.2004.04945.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic graft versus host disease

Abstract: SummaryThe ability to cure increasing numbers of individuals for malignant and non-malignant diseases with the use of stem cell transplantation has resulted in a growing number of long-term survivors with unique medical issues. Chronic graft versus host disease (GvHD) continues to be a significant problem in the allogeneic stem cell transplant setting and, as we continue to use alternative stem cell sources and attempt to modulate the immune system to increase an anti-tumour effect, we will probably see rising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 139 publications
(133 reference statements)
2
116
0
3
Order By: Relevance
“…For this reason, this grading system, although highly reproducible and useful for clinical decision making as to whether to initiate treatment, provides only limited information on the prognosis of patients. 10,11 Several clinical and biologic features have been identified as prognostically significant in previous studies of cGVHD, including categorization as extensive cGVHD, 9,12 Karnofsky performance status (KPS), 12 thrombocytopenia (o100 000 mm 3 ), 12,13 progressive-type onset of cGVHD, 14 lichenoid histology, 14 and elevated bilirubin. 14 According to recently introduced new clinical grading systems for cGVHD, 10,11 thrombocytopenia, progressive-type onset, and extensive skin GVHD, involving more than 50% of body surface area at the diagnosis of cGVHD, are independent risk factors affecting relapse-free survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, this grading system, although highly reproducible and useful for clinical decision making as to whether to initiate treatment, provides only limited information on the prognosis of patients. 10,11 Several clinical and biologic features have been identified as prognostically significant in previous studies of cGVHD, including categorization as extensive cGVHD, 9,12 Karnofsky performance status (KPS), 12 thrombocytopenia (o100 000 mm 3 ), 12,13 progressive-type onset of cGVHD, 14 lichenoid histology, 14 and elevated bilirubin. 14 According to recently introduced new clinical grading systems for cGVHD, 10,11 thrombocytopenia, progressive-type onset, and extensive skin GVHD, involving more than 50% of body surface area at the diagnosis of cGVHD, are independent risk factors affecting relapse-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…The most important factor is the presence of prior aGVHD, which has been repeatedly identified in several studies. [2][3][4][5][6][7] Other factors include older age, diagnosis of chronic myelogenous leukemia, female donor to male recipient, and the use of an unrelated donor. 2,4,6,7 A recent meta-analysis confirmed that use of peripheral blood stem cells significantly increases the risk of cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…cGVHD is thought to be closely associated with aGVHD, but recent studies indicate that besides the time of onset, cGVHD and aGVHD differ both clinically and pathobiologically. 34,35 In addition, aGVHD does not necessarily develop into cGVHD, nor does cGVHD necessarily follow aGVHD. Moreover, cGVHD involves pathogenic autoreactivity in addition to alloreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10,12,13,20 Several scholars indicated that use of mismatched or unrelated donors was a risk factor for cGVHD. 20 However, Teshima et al 21 only noted a tendency for increasing cGVHD with increasing HLA disparity, rather than a statistically significant correlation (P ¼ 0.05); other studies found that the occurrence of cGVHD did not differ between patients receiving ISD vs HID/PMRD HSCT, 22,23 which may be due to the usage of ATG in these studies. Several studies observed that the incidence of cGVHD and extensive cGVHD decreased sharply (23 --40% and 23 --26%, respectively) in patients treated with ATG compared with patients treated without ATG.…”
Section: Sf-36 Scoresmentioning
confidence: 99%